A Proposed Model for the Relationship between the Key Competitive Forces and the Differentiation Strategy in the Egyptian National Universities The Mediation Effect of Market Orientation - Omar, Gihan Ahmed (The Arab Journal of Administration, 2024)
Purpose: The purpose of the paper is to investigate the impact of the key competitive forces which are the intensity of rivalry, bargaining power of suppliers, bargaining power of buyers, Government regulations, and Technology forces on the differentiation strategy in the Egyptian national universities considering the mediation effect of market orientation. Design/ Methodology/ Approach: This paper used a quantitative research design. The census method was adopted. A self-administered questionnaire was developed to collect data from all academics and administrators who hold leadership positions at the four main Egyptian national universities namely: Elgalala, International King Salman, Elmansora, Elgededa and Elaalameen , Egededa. Data was analyzed through SPSS-Statistics software 23.0 versions and Amos Application-25. Findings: The findings of this research indicated that the direct impact of the intensity of rivalry, the bargaining power of suppliers and the technology force on the differentiation strategy have been proved while it was not confirmed for the bargaining power of buyers and the government regulations indicating the importance of the mediating variable which is market orientation in enhancing this relationship. Originality/ Value: This study is the first to look at the relationship between the key competitive forces and the differentiation strategy whether directly or indirectly by mediating market orientation in the higher education industry in both Egypt and the Arab region.